Integração da farmacogenética do tacrolimo ao gerenciamento da terapia medicamentosa em transplantados renais. - Isabela Diniz Gusmão de Oliveira (2022)
Tacrolimus is part of the maintenance immunosuppression regimen in renal transplantation, but due to its narrow therapeutic range, serum monitoring is recommended. The enzyme CYP3A5 performs metabolism of tacrolimus and polymorphisms in this gene alter its pharmacokinetics. Thus, individuals with at least one functional allele *1 are called CYP3A5 expressors (CYP3A5 *1/*1 and *1/*3), and the others are not expressors (CYP3A5 *3/*3). The identification of polymorphisms in the CYP3A5 gene may be a complementary strategy to the management of drug therapy. The objective of the present study was to use pharmacogenetic data to assist in the clinical and situational assessment of renal transplant patients using tacrolimus in Medication Therapy Management, in order to improve the effectiveness and safety of pharmacotherapy. Initially, a systematic review was performed to identify genetic polymorphisms that influence the pharmacokinetics of tacrolimus. At the same time, an observational study was carried out to describe the Medication Therapy Management service in a transplant clinic of a hospital in Belo Horizonte, Minas Gerais, as well as the analysis of polymorphisms in the variant alleles CYP3A5*3, *6 and *7. The systematic review showed other polymorphisms that interfere with the pharmacokinetic parameters of tacrolimus, but only in the CYP3A5 gene were significant short-term clinical outcomes found. In the observational study, 70 patients were included, of which 42 were on Medication Therapy Management, 41 (58.6%) were male, 22 (33.8%) were aged between 31 and 40 years, 40 (71, 4%) received a kidney from a deceased donor and 34 (52.3%) were between 6 and 9 months posttransplant. A higher serum concentration of tacrolimus was observed in CYP3A5 expressors, but no change in the mean dose of this drug between the groups. Regarding the frequency of drug-related problems, it was observed that 11 (27.%) patients had none, 19 (47.5%) had only one, and 5 (12.5%) had two or three, and none related to the immunosuppressive regimen. Therefore, the use of pharmacogenetic data can be useful to optimize tacrolimus pharmacotherapy in the context of Medication Therapy Management, helping the multidisciplinary team to make decisions related to effectiveness, safety and adherence.